2020
DOI: 10.1103/physrevmaterials.4.114007
|View full text |Cite
|
Sign up to set email alerts
|

Spatially correlated incommensurate lattice modulations in an atomically thin high-temperature Bi2.1Sr1.9CaCu2.0O8+

Abstract: We report Scanning nano X-ray Diffraction (SnXRD) imaging of incommensurate lattice modulations in Bi2.1Sr1.9CaCu2.0O8+δ Van der Waals heterostructures of thicknesses down to two-unit cells. Using SnXRD, we probe that the long-range and short-range incommensurate lattice modulations in bulk sample surface with spatial resolution below 100 nm. We find that puddle-like domains of ILM of size uniformly evolving with dimensionality. In the 2-unit cell thin sample, it is observed that the wavevectors of the long-an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
(45 reference statements)
2
7
0
Order By: Relevance
“…Therefore, η = 9/ε = 4x + 5y varies in the range 36 < η < 45 and at each integer value of η the system reaches a quasi-commensurate phase at each step of a devil's staircase. We have found that in the BSCCO samples, where the chemical potential is tuned by the concentration of oxygen interstitials, the mismatched XCuO 2 bilayer is tuned by the misfit strain at the quasi-commensurate modulation with η = 43 i.e, ǫ=9/43 = 0.209 in agreement with the recent scanning micro-X-ray diffraction 34 which is the devil's staircase for x = 2 and y = 5, therefore we have 4 × 2 + 5 × 7 = 43 (i.e. a quasicrystal made of 8 insulating lattice units and 35 metallic lattice units).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, η = 9/ε = 4x + 5y varies in the range 36 < η < 45 and at each integer value of η the system reaches a quasi-commensurate phase at each step of a devil's staircase. We have found that in the BSCCO samples, where the chemical potential is tuned by the concentration of oxygen interstitials, the mismatched XCuO 2 bilayer is tuned by the misfit strain at the quasi-commensurate modulation with η = 43 i.e, ǫ=9/43 = 0.209 in agreement with the recent scanning micro-X-ray diffraction 34 which is the devil's staircase for x = 2 and y = 5, therefore we have 4 × 2 + 5 × 7 = 43 (i.e. a quasicrystal made of 8 insulating lattice units and 35 metallic lattice units).…”
Section: Introductionsupporting
confidence: 87%
“…Spatially correlated incommensurate lattice stripy modulations in Bi 2 Sr 2 CaCu 2 O 8+y superconductor can now be visualized by the scanning submicron X-ray diffraction focusing on the superlattice satellites of the main X-ray reflections [32][33][34] . The results show that, while oxygen concentration and the doping level can change depending on the sample treatments and thermal history, the incommensurate superlattice wavevector is controlled by the misfit strain and it exhibits a remarkable stability.…”
Section: Introductionmentioning
confidence: 99%
“…at low temperatures seen in recent experiments [46]. The high value of the critical current of the twist junction observed in experiment [46] also indicates that the momentum relaxation is arising from nanoscale inhomogeneities, such as ones that arise from structural supermodulation [60], and not atomic-scale disorder. This is consistent with the atomically sharp interfaces with structural supermodulations observed using transmission electron microscopy in Ref.…”
Section: (T )/Imentioning
confidence: 86%
“…For the more realistic case of weak nanoscale disorder (such as structural supermodulations [60]), with a length scale significantly larger than the unit cell size, the tunneling has a characteristic momentum spread that is smaller than the size of the Brillouin zone. We consider the case where tunneling is not exactly momentum conserving, modeled with a spread of σ in typical momentum differences |k − k |.…”
Section: Effects Of Interface Inhomogeneity On Ic(θ0 T )mentioning
confidence: 99%
“…Figure 1D shows cross-sectional high-angle annular dark field (HAADF) scanning transmission electron microscope (STEM) image of a θ = 46° junction, simultaneously viewing both BSCCO crystals on two different zone axes. Notably, crystalline order is maintained at the interfacial layer with no change to the lattice structure ( 35 ) in the [001] direction between atomic layers (Fig. 1E) or along CuO 2 planes (Fig.…”
Section: Building Twisted Bscco Junctionsmentioning
confidence: 99%